Tranexamic Acid: Role in Prevention of Post Partum Hemorrhage (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objective of the study was to compare the frequency of postpartum hemorrhage in patients given tranexamic acid along with active management of third stage of labor versus the control group in which active management of third stage of labor alone was done. Study Design: Randomized controlled trial Place and duration of study: This study was conducted in the Department of Obstetrics and Gynaecology, Unit II Sheikh Zaid Medical Hospital Rahim Yar Khan from January 2015 to October 2015. Patients and methods: Eight hundred and twenty patients presenting in labor and fulfilling the inclusion criteria were included in this study. Patients were divided into two groups, cases and control. Each group had 410 patients. Cases were included those patients in which active management of third stage of labor was done, in addition they received intravenous 1gm tranexamic and control group received only active management of third stage of labor. Results: As compared to active management of third stage of labor alone, addition of tranexamic acid was responsible for significant reduction in frequency of PPH and amount of blood loss( P value
Keywords: Tranexamic acid, postpartum hemorrhage, active management of third stage of labor